Power system transient stability enhancement - Liu, Chengqi (2016)
In power system control, enhancing power transient stability under large disturbance is one of the most widely studied properties of power system control. Power system transient stability is essential for ensuring the quality of power delivering and transmission. In order to improve power transient stability, AVR, PSS and PID controllers are popular to use for enhancing performance of the power system. Especially PID controllers are still widely used even today for their simplicity to control and extensive research in a wide range of research areas. The performance of the power system transient stability will be demonstrated in MATLAB/Simulink.